2007
DOI: 10.1590/s0001-37652007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Heavy mineral as a tool to refine the stratigraphy of kaolin deposits in the Rio Capim Area, Northern Brazil

Abstract: Studies of heavy minerals in kaolin deposits from the Ipixuna Formation in the Rio Capim area (Northern Brazil) showed a mature to super mature assemblage dominated by zircon and tourmaline, and subordinately rutile, kyanite and staurolite. These minerals do not change much throughout the whole section; however, each kaolin unit displays a particular signature, defined by differences in the proportions of the whole assemblage of heavy minerals, as well as of their textural characteristics. This work revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Sousa et al (2007a) using geochronological data from several zircon grains extracted from both soft and flint kaolin found two distinct source areas for the kaolin-bearing sediments, which confirmed the lateritic origin of kaolin. This agrees with earlier contributions and yet is in disagreement with Góes et al (2007), who used the data of heavy minerals to discredit lateritic weathering for the kaolin deposits.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…Sousa et al (2007a) using geochronological data from several zircon grains extracted from both soft and flint kaolin found two distinct source areas for the kaolin-bearing sediments, which confirmed the lateritic origin of kaolin. This agrees with earlier contributions and yet is in disagreement with Góes et al (2007), who used the data of heavy minerals to discredit lateritic weathering for the kaolin deposits.…”
Section: Introductionsupporting
confidence: 83%
“…Santos et al (2007) conducted d 18 O and d D analyzes on kaolinites originating from soft and hard (semi-flint) kaolin from Rio Capim deposits and concluded that kaolinites were not in equilibrium with modern weathering processes. These authors concluded that kaolinites must have been formed during different phases of paleoweathering (Santos et al, 2007), which is in contradiction to Santos and Rossetti (2003), Rossetti and Santos (2006) for flint kaolin and Góes et al (2007), who have all supported the argument of sedimentary deposition. Recently, Sousa et al (2007b) offered new insights regarding the chemical, mineralogical and micromorphological characteristics and origins of kaolin deposits.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Deposits from Rio Capim and their chemical analysis indicated intense lateritic processes, characterized by ferruginization and deferruginization, that created the several facies (Souza et al, 2006). Studies involving heavy minerals from the Rio Capim area indicated that the age of the kaolin deposits from Ipixuna Formation is Late Cretaceous (Góes et al, 2007). Rio Jari and Rio Capim are areas where sedimentary kaolin deposits are mined and their ages are, respectively, Pliocene and Tertiary (Murray et al, 1982;Murray et al, 2007).…”
Section: Introductionmentioning
confidence: 99%